Bioethics Reenvisioned : A Path Toward Health Justice. - King, Nancy M. P. (University of North Carolina Press, 2022)
"Bioethics needs an expanded moral vision. It is now time for bioethics to take full account of the problems of health disparities and structural injustice that are made newly urgent by the COVID-19 pandemic and the effects of climate change. Nancy M. P. King, Gail E. Henderson, and Larry R. Churchill make the case for a more social understanding and application of justice, a deeper humility in assessing expertise in bioethics consulting, a broader and more relevant research agenda, and greater appreciation of the profound health implications of global warming"-- Provided by publisher.
Keywords: Bioethics.; Medical ethics -- Social aspects.; Health services accessibility.; Social justice.; COVID-19 Pandemic, 2020-; Health Services Accessibility.; Social Justice.; Éthique médicale -- Aspect social.; Services de santé -- Accessibilité.; Justice sociale.; Pandémie de COVID-19, 2020-; MEDICAL / Ethics; Bioethics; Health services accessibility; Medical ethics -- Social aspects; Social justice; Since 2020; Electronic books.